2005
DOI: 10.1074/jbc.m409381200
|View full text |Cite
|
Sign up to set email alerts
|

SMAD and p38 MAPK Signaling Pathways Independently Regulate α1(I) Collagen Gene Expression in Unstimulated and Transforming Growth Factor-β-stimulated Hepatic Stellate Cells

Abstract: The hepatic stellate cell (HSC) is the predominant cell type responsible for excess collagen deposition during liver fibrosis. Both transforming growth factor-␤ (TGF-␤), the most potent fibrogenic cytokine for HSCs, which classically activates Smad signaling, and p38 MAPK signaling have been shown to influence collagen gene expression; however, the relative contribution and mechanisms that these two signaling pathways have in regulating collagen gene expression have not been investigated. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(125 citation statements)
references
References 45 publications
4
120
1
Order By: Relevance
“…Other reports frequently instead demonstrated that such p38 activation peaks occurred at earlier time points, that is, 15 min to 2 h, depending on cell types. 43,44 Although we are unable to explain this discrepancy, it is possible that this difference could be explained by the finding that protein phosphatase-2A, which is potentially activated by TGF-b, might dephosphorylate activated p38 at early times. 45 However, we failed to examine whether the mechanism of p38 phosphorylation at the peak of 6 h was induced by the direct effect of binding TGF-b2 to the receptor or by secondary effects of other growth factors induced by TGF-b2.…”
Section: Discussionmentioning
confidence: 51%
“…Other reports frequently instead demonstrated that such p38 activation peaks occurred at earlier time points, that is, 15 min to 2 h, depending on cell types. 43,44 Although we are unable to explain this discrepancy, it is possible that this difference could be explained by the finding that protein phosphatase-2A, which is potentially activated by TGF-b, might dephosphorylate activated p38 at early times. 45 However, we failed to examine whether the mechanism of p38 phosphorylation at the peak of 6 h was induced by the direct effect of binding TGF-b2 to the receptor or by secondary effects of other growth factors induced by TGF-b2.…”
Section: Discussionmentioning
confidence: 51%
“…Zinc inhibited both JNK phosphorylation and HSC migration. It has also been detected that the inhibiting of either p38 MAPK or Smad signaling reduces 1(I) collagen gene expression in untreated HSCs, and when both signaling pathways are simultaneously inhibited, 1(I) collagen gene expression is essentially blocked [63]. These data indicate that not only MAPK pathways but also TGF--induced signaling is important in the activation of HSCs.…”
Section: Discussionmentioning
confidence: 90%
“…ERK, p38, phosphatidylinositol 3-kinase) (56), an increase in pERK1/2 and pp38 was observed in the presence of TGF␤. AdoMet pretreatment prevented the phosphorylation of ERK1/2 but not of p38.…”
Section: Induction Of Liver Fibrosis In Mouse Col1a2 Promoter Transgementioning
confidence: 97%